Shakespeare and women - Rackin, Phyllis (Oxford Shakespeare topics., 2005)
Shakespeare and Women challenges a number of current assumptions about Shakespeare and women, including the women in his family, the women who worked in the London theatre industry, the female characters in his plays, and the dark lady of the Sonnets. It argues that the current scholarly emphasis on patriarchal power, male misogyny, and women's oppression may tell us more about ourselves than about the world Shakespeare inhabited and the worlds he created in his. plays. - ;Shakespeare and Women situates Shakespeare's female characters in multiple historical contexts, ranging from the early mod.